2013
DOI: 10.5296/jsr.v4i1.3294
|View full text |Cite
|
Sign up to set email alerts
|

Rational Choice Theory and the Choice of Healthcare Services in the Treatment of Malaria in Nigeria

Abstract: This paper is on the rational choice theory and the choice of healthcare services for the treatment of malaria in Nigeria. It focuses on the factors that influence or determine the choice malaria treatment using the rational choice theory as the basis. It was discovered that there were many determinants of what informs the maximum utility but it is all wrapped up in the organization of the health care system. Hence, in choosing treatment for malaria, factors like; perceived and actual quality of care, proximit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, while thematic analysis is adaptable, this adaptability can lead to inconsistencies in the development of themes. The study's claims were supported by rational choice theories, which fostered consistency (Owumi, B. E, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, while thematic analysis is adaptable, this adaptability can lead to inconsistencies in the development of themes. The study's claims were supported by rational choice theories, which fostered consistency (Owumi, B. E, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…Again, providing effective, accessible and affordable health care to those who are already enrolled into the NHIS has also remained a serious challenge (Inoughele and Mohammed, 2013;Owumi and Sakiru, 2013). And more importantly, Federal Government of Nigeria (FGN (2015) had actually corroborated the findings from other studies, when it reported that some challenges confronting the implementation of the NHIS during its decade of existence include (a) exclusion of certain categories of people in its benefit package; (b) low coverage across the country due to low health-seeking behavior; (c) low uptake by states and local government employees; (d) limit of free health protection programme for the poor and vulnerable; and (e) weak stakeholder responsibility.…”
Section: Access To Healthcare Under the Nhismentioning
confidence: 99%
“…Rational choice theory is to make optimal and seasoned choose for solving the problem or achieving the goal. Rational Choice Theory presumes that individuals' choice for the problem is representative of larger group so it always begins with the consideration of individual decision-making units' choice behavior (19). Although individuals cannot control all the relevant factors, the choice they made that can best help achieve the goals (20).…”
Section: Political Theorymentioning
confidence: 99%